Regional macroeconomic outcomes under alternative arrangements for the financing of urban infrastructure - Peter Dixon; James Giesecke; Maurreen Rimmer (European Regional Science Association (ERSA), 2004)
Many studies, both of Australia and of comparable developed economies, have found that the economic benefits from investment in urban infrastructure are substantial. However the nature of this infrastructure is often such that it is under-provided by the private sector. In Australia, much of the responsibility for the provision of urban infrastructure rests with state and local government. However throughout the 1990's many of Australia's state governments embarked on a period of fiscal restraint, seeking to improve financial positions weakened by exposure to failed state government enterprises in the early 1990's. Perhaps because of the deferred consequences of reducing spending on infrastructure, a large proportion of this fiscal adjustment appears to have been borne by spending on public infrastructure. Today, policy attention at the state government level is again focussing on public infrastructure. However in spite of the now robust fiscal positions of Australia's state governments, there remains a reluctance on their part to finance public infrastructure through debt, and raising taxes is perceived as politically unpopular. Instead, governments are exploring alternative financing instruments, such as developer charges and public-private partnerships. This paper uses a dynamic multi-regional CGE model (MMRF) to evaluate the regional macro economic consequences of four alternative methods of financing an expansion in state government spending on public infrastructure. The four methods are developer charges, payroll tax, government debt, and residential rates. The paper confirms that the services provided by public infrastructure can have significant impacts on the regional macro economy. More importantly however, the paper demonstrates that the total gains from urban infrastructure are quite sensitive to the means chosen by government to finance infrastructure investment. In contrast to up-front financing methods (such as developer charges, payroll tax, and residential rates), the paper finds that the gains from urban infrastructure are greatest when the chosen financing method provides a closer match between the timing of the burden of financing the infrastructure and the timing of the benefits provided by the infrastructure. This can be achieved by instruments such as debt, public-private partnerships, and user charges. On this basis the paper finds that a greater reliance by regional government son debt financing might be warranted, and that the gains from infrastructure expenditure are least when that expenditure is financed by developer charges.
Keywords: 330